2006
DOI: 10.2353/ajpath.2006.060037
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Murine Skin Responses to UV-B Light Are Partially Dependent on Endothelin-1 and Mast Cells

Abstract: Endothelin (ET-1) has been shown to crucially contribute to UV-induced skin responses such as tanning.To test whether ET-1 is also involved in early cutaneous reactions to UV, we assessed ET-1 skin levels in UV-irradiated mice. In correlation with the levels of UV-induced skin inflammation, ET-1 concentrations increased substantially and continually. Moreover, blocking of ET-1 receptors (ET A ) resulted in significantly decreased cutaneous inflammation following UV irradiation. When we assessed skin responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 33 publications
0
41
2
Order By: Relevance
“…In the response to sunburn, MC activation has been demonstrated to be accompanied by a rapid degranulation of cutaneous MCs (Gilchrest et al, 1981;Walsh, 1995). More recently, we have shown that this MC activation after UVB irradiation does contribute, at least in mice, significantly to the inflammation following a severe sunburn (Metz et al, 2006a). Although the activation of MCs in this setting initially contributes to the pathology of excessive UV light exposure, i.e.…”
Section: Skin Mast Cells Sense and React To Immediate Dangermentioning
confidence: 77%
See 1 more Smart Citation
“…In the response to sunburn, MC activation has been demonstrated to be accompanied by a rapid degranulation of cutaneous MCs (Gilchrest et al, 1981;Walsh, 1995). More recently, we have shown that this MC activation after UVB irradiation does contribute, at least in mice, significantly to the inflammation following a severe sunburn (Metz et al, 2006a). Although the activation of MCs in this setting initially contributes to the pathology of excessive UV light exposure, i.e.…”
Section: Skin Mast Cells Sense and React To Immediate Dangermentioning
confidence: 77%
“…Skin MCs from mice and humans on the other hand share many characteristic features (Table 1), e.g. they are both preferentially localized in close proximity to hair follicles and blood vessels (Weber et al, 2003;Paus et al, 2006b), their numbers increase similarly in chronic skin inflammation and they are known to respond to the same physical and biochemical stimuli (Metz et al, 2006a;Theoharides and Kalogeromitros, 2006). Because of these similarities it can be hypothesized that the essential role of murine skin MCs in certain innate immune responses described above may be of similar importance in the human system.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Indeed, the effects of both donor T cells and UV irradiation are pleiotropic. UV irradiation causes acute cell death and local inflammation, [49][50][51][52] and alloreactive T cells induce systemic cytokines and local inflammation in skin and can directly target nonhematopoietic and hematopoietic cells in addition to LCs. Our finding that donor LCs engrafted in Langerin-DTA recipients, which have a very specific loss of only LCs, 23 without the need for allogeneic T cells or UV irradiation indicates that skin inflammation per se is not required for donor LC engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the subsequent skin inflammation requires the activation by ET-1, which is increased to amounts comparable with those seen after PA infection. 33 ET-1 is only one of many candidate signalswhich also include other neuropeptides and complement mice (n ϭ 9 -32), and Kit W /Kit W-v mice (n ϭ 9 -27) injected subcutaneously with PA. Skin was harvested 24 hours after subcutaneous infection with PA. Histological sections were processed for H&E staining and imaged at ϫ50 (D-F) and ϫ400 (G-I) magnification.…”
Section: Discussionmentioning
confidence: 99%